Performance evaluation of pomegranate (Punica granatum) genotypes under saline conditions - Rajkumar, Rajkumar; Singh, Anshuman; Mann, Anita; Yadav, R K (The Indian Journal of Agricultural Sciences, 2020)
Pomegranate (Punica granatum L., family: Lytheraceae) is widely grown in arid and semi-arid areas across the globe, where moderate or relatively high salt concentration in the soil negatively affect the plant growth properties. However, there is scarce information on the response of pomegranate cultivars under saline field conditions. Therefore, this experiment was conducted in a saline field (soil ECe 6-8 dS/m, ECiw 3.9-4.2 dS/m) during two consecutive years (2017-18) at Nain Experimental Farm, Panipat, India to study the effects of salinity on vegetative growth and fruit quality traits in 15 genotypes of pomegranate. The experiment was laid out in Randomized Block Design with four replications. Analysis of Variance revealed highly significant differences among the genotypes for fruit growth and quality traits. Results showed considerable variation in the plant growth and fruit quality traits of the pomegranate genotypes. Our findings indicated that fruit quality traits like fruit weight, juice percentage, number of arils, and aril colour could be used as criteria for selecting promising pomegranate genotypes for salt-affected soils. Overall, genotypes Udaipur 2, Udaipur 3, Rajasmand 4 and Jaipur 1 seem to be more tolerant of salinity stress than other genotypes and thus have potential for cultivation in saline soils.